2015
DOI: 10.1186/s12889-015-2672-7
|View full text |Cite
|
Sign up to set email alerts
|

The art of being mentally healthy: a study to quantify the relationship between recreational arts engagement and mental well-being in the general population

Abstract: BackgroundLittle is known about the dose–response relationship between recreational arts engagement (for enjoyment, entertainment or as a hobby, rather than therapy) and mental well-being in the general population. The quantification of this relationship is of value to: (1) health professionals, clinicians and researchers interested in utilising the arts as a method for improving mental health; (2) to health promoters and policy makers in the development of population based health messages, policy and practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 34 publications
5
83
0
Order By: Relevance
“…With an emphasis on self-expression, creativity, enjoyment and social inclusion the arts are receiving increasing attention as a means of promoting health and mental health (Davies, Knuiman, & Rosenberg, 2015). The importance of creative art in contributing to the YP's mental wellbeing is beginning to be understood and pursued as part of public health initiatives and interventions which aim to reduce stigma and promote recovery.…”
Section: Discussionmentioning
confidence: 99%
“…With an emphasis on self-expression, creativity, enjoyment and social inclusion the arts are receiving increasing attention as a means of promoting health and mental health (Davies, Knuiman, & Rosenberg, 2015). The importance of creative art in contributing to the YP's mental wellbeing is beginning to be understood and pursued as part of public health initiatives and interventions which aim to reduce stigma and promote recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Western Australian study found, after adjustment for covariates (i.e. age, sex, location, income, education, marital status, children, general health, sports engagement, religious activities and holidays), that two or more hours per week of arts engagement was associated with better mental wellbeing than those with none or lower levels of engagement ( p =0.003) 22 . If this association is found to be causal, then this study could be a starting point for dose–response, time‐related health messages and public health strategies related to the arts (i.e.…”
Section: What Is Arts and Health?mentioning
confidence: 99%
“…A population based study showed evidence of an existing arts engagement-mental health relationship, where those who engaged in arts activities 100 hours yearly or more reported significantly better mental well-being than others [9]. A number of British projects offered Arts on Prescription for people experiencing mental health problems and social isolation, and the results proved to help people recover [8].…”
Section: Possible Link Between Cultural-literary Activities Health Amentioning
confidence: 99%